Pedagogy of the oppressed: education and citizenship in the wanderings of the paths Brazil / Portugal (Cadernos de Sociomuseologia, 2022)
This is a dialogue walked along the paths of Paulo Freire, having as its thread the Pedagogy of the Oppressed, woven to compose our process of formation, research and sharing. Our “gentification” starts from our ground (Brazil) in webs and experiences involving teaching, research and knowledge production, where the people speak the word and write their life, in a process that intertwines with our narrative of a militant and apprehensive educator, in the Brazil and Portugal, composing our mandala life with the Grail Movement and its relationship with Freire, on the path of Education and Citizenship before the April Revolution (1970/1974). Our biography is composed in the meetings and learning, interconnecting the process of our journey where Paulo Freire is a reference and north, being methodological support and inspiration in training processes in Public School and in spaces within the Social Movement. Composing the “viable unprecedented”, we walk in a question methodology, registered in the life stories told by protagonists who develop an educational process, paths and encounters with Freire here and there, “gentifications”, “weavings”, wanderings, encounters with sociomuseology and the wanderings that allow meetings and sharing in Brasil and Portugal.Key words: Education; Citizenship; Awareness; GRAAL ; Sociomuseology